A Scene of Exception: neotechnological theater in Belo Horizonte (Brazil) and Buenos Aires (Argentina) - Muniz (Universidade Federal de Minas Gerais – UFMG, Belo Horizonte/MG, Brazil), Mariana Lima; Dubatti (Universidad de Buenos Aires – Buenos Aires, Argentina), Jorge (Revista Brasileira de Estudos da Presença, 2022)
This paper examines theater shows Play Me by Rodrigo Campos, premiered in Belo Horizonte, and Distancia by Matías Umpierrez and Las Ideas by Federico León, premiered in Buenos Aires. In the three shows, elements of digital media are used to momentarily replace the physical presence of actors. The micro-poetics of these productions are exceptions in the theatrical scene of two cities known for a lively theater scene, in which the coexistence of spectators and performers in the same space is appreciated. As exceptions, however, they shed light on an idiosyncrasy of the theater present in the two cities in relation to the neotechnological scene: the appreciation of coexistence and copresence despite the absence introduced by the use of novel technologies.